1996
DOI: 10.1046/j.1365-2249.1996.d01-800.x
|View full text |Cite
|
Sign up to set email alerts
|

Thy-1 molecule associates with protein tyrosine kinase(s) in rat mesangial cells

Abstract: SUMMARYGlycophosphatidylinositol (GPI)-linked Thy-1 molecules, well known cell surface markers of murine T cells, are present on the glomerular mesangial cells of the rat kidney. The administration of anti-Thy-1.1 MoAbs 1-22-3 and OX-7 to rats induces severe and mild complement-dependent mesangial proliferative glomerulonephritis, respectively. In order to determine whether protein-tyrosine kinase (PTK) activity is associated with Thy-1 molecules on rat mesangial cell surface, we performed an immune complex ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Thy-1 also may function as an adhesion molecule in other cells, including T cells [41]. We previously showed that Thy-1.1-mediated signal transduction via the Src-mediated protein tyrosine kinase and phosphatidylinositol turnover is triggered differentially by 1-22-3 and OX7 [13, 14]. The epitopes or domains of Thy-1.1 molecule important in different aspects of mesangial cell function, such as cell adhesion, migration, and differentiation, remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thy-1 also may function as an adhesion molecule in other cells, including T cells [41]. We previously showed that Thy-1.1-mediated signal transduction via the Src-mediated protein tyrosine kinase and phosphatidylinositol turnover is triggered differentially by 1-22-3 and OX7 [13, 14]. The epitopes or domains of Thy-1.1 molecule important in different aspects of mesangial cell function, such as cell adhesion, migration, and differentiation, remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have recently demonstrated a physical association of protein tyrosine kinases, p59 fyn and p56/53 lyn, with Thy-1.1 molecule in cultured rat mesangial cells, and the activities were observed to be higher than those in mAb OX7 precipitates [13]. We have also reported the two to three times higher inositol triphosphate production and a greater response in Thy-1.1-mediated increase in intracellular free calcium concentration by 1-22-3-treated than OX7-treated mesangial cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…Thy-1 has been co-immunoprecipitated with the SFK Fyn from noncaveolar rafts in PC 12 cells and with active Fyn and Lyn SFKs in mesangial cells (34,35). Two models have been described for Thy-1-SFK interaction.…”
Section: Thy-1 Required For Tsp-1-mediated Focal Adhesion Disassemblymentioning
confidence: 99%
“…Apoptosis induced via triggering of Thy-1 has previously been demonstrated for mouse thymocytes, which could be inhibited by addition of the tyrosine kinase inhibitor herbimycin. Interestingly, in rat mesangial cells, Thy-1 was shown to be associated with tyrosine kinases as well [19], and mAb-mediated triggering of mesangial Thy-1 induced an increase in the intracellular calcium concentration that could be blocked by herbimycin [20]. …”
Section: Cross-linking Of Thy-1 Induces Apoptosis In Cultured Mesangimentioning
confidence: 99%